2017
DOI: 10.1038/s41598-017-01181-w
|View full text |Cite
|
Sign up to set email alerts
|

White spot syndrome virus VP28 specific double-stranded RNA provides protection through a highly focused siRNA population

Abstract: Several studies have demonstrated that injection of double-stranded RNAs (dsRNA) homologous to mRNA for the white spot syndrome virus (WSSV) viral protein 28 (VP28) can induce protection in shrimp against WSSV through RNA interference (RNAi). In comparison to shrimp injected with either PBS or a green fluorescent protein (GFP) nonspecific dsRNA, we obtained nearly complete protection against WSSV infection in shrimp injected with VP28 dsRNA. Upregulation of host genes associated with small RNA silencing was me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…The maximum dose used in the present work was 3.0 µg/shrimp with 95% protection at 504 hpi (21 days). These evaluated doses are lower than those previously reported from 5.5 μg doses [66] up to 31 μg of dsRNA/shrimp [23]. This work has demonstrated the efficacy of the dose, and the sequence of the dsRNA used.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The maximum dose used in the present work was 3.0 µg/shrimp with 95% protection at 504 hpi (21 days). These evaluated doses are lower than those previously reported from 5.5 μg doses [66] up to 31 μg of dsRNA/shrimp [23]. This work has demonstrated the efficacy of the dose, and the sequence of the dsRNA used.…”
Section: Discussionmentioning
confidence: 53%
“…The RNAi trials using an intramuscular injection (IM) have shown that VP28 glycoprotein is the target of choice to block WSSV infection in shrimp [14,23,24]. However, RNAi intramuscular (IM) administration is limited to lab-scale experiments since its use is not yet viable for applications on a large scale, as found in salmon farms [25].…”
Section: Introductionmentioning
confidence: 99%
“…RNA interference (RNAi) is an endogenous gene-silencing mechanism that can be repurposed to combat viral infection through sequence-specific recognition and degradation of viral RNA [ 10 ]. As one of the most infamous shrimp viruses, RNAi applications against White Spot Syndrome Virus (WSSV) have been extensively investigated [ 11 , 12 ] and dsRNA targeting the VP28 mRNA, which encodes the virus envelope protein that has been implicated in host entry [ 13 , 14 ], has become one of the most effective targets [ 15 ]. Despite the promising results at a laboratory level, the implementation of the RNAi technology at a farm level is still at its infantile stage due to the lack of effective delivery approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this envelop protein plays significant role in initiating the WSSV infection in shrimp [22]. The VP28 gene of the WSSV is suggestively involved in endosome escape through its interaction with host Rab7 [24], and has been identified as a potent target for dsRNA treatment in comparative studies [25]. Previous analyses of strain variability reported that competitive fitness depends on the size of the genome [26,27], however, these studies are far from enough to illustrate the mechanisms of WSSV pathogenesis.…”
Section: Introductionmentioning
confidence: 99%